SETTING LIQUID LEVEL COUPLED TANK USING FUZZY ADAPTIVE CONTROL - Mohammad Erik Echsony; Noorsakti Wahyudi; Nur Asyik Hidayatullah (JEEMECS (Journal of Electrical Engineering, Mechatronic and Computer Science), 2018)
Problem with Coupled Tanks is the appearance of interference in the flow that supplies the tank will make the response unstable, resulting in cross-interaction between each input and output. Fuzzy Logic Control (FLC) has its own advantages that is effective in dealing with complex non-linear systems. Adaptive Fuzzy control Auto tuning has the ability to maintain the steady state response value from interference. Adaptive Fuzzy methodology is attractive choice when formulation in the method proposed for the Coupled tank process. Adaptive Fuzzy control has the ability to maintain the steady state response value from interference. In this study using decoupling in the cross interaction process in each tank. Coupled Tanks on the TITO system can change the transfer function to SISO, so as to minimize the effect of interacting. The right way to design modeling is to pay attention to the state of the plant, so that the desired control model can overcome the non linearity of the TITO system. Adaptive Fuzzy method expected to have percent overshoot and better settling time value.DOI : https://doi.org/10.26905/jeemecs.v1i2.2423